Analysis of the Level of Compliance of Corporate Taxpayers in Reporting PPN Period SPT Using E-Invoice 3.0 on Tax Revenue Performance at KPP Pratama Manado - Sutri ELEM; Lintje KALANGI; Claudia W.M. KOROMPIS (PT Keberlanjutan Strategis Indonesia, 2023)
Taxpayer compliance plays an important role in tax revenue. The more taxpayers are obedient in paying taxes, the greater the tax revenue received. The development of information systems and technology in the taxation sector continues to be carried out by the government to ensure compliance and accountability in tax collection. One of them is a change in the tax administration system or what is commonly called tax system modernization. In order to improve the ease of service to PKP, the Directorate General of Taxes released the latest e-invoice application, namely e-invoice 3.0. The e-faktur 3.0 application has a variety of the latest automation features which certainly make it easier for PKP to submit Periodic VAT Returns in only one application, namely e-faktur 3.0. This study aims to determine the level of compliance of corporate taxpayers in reporting Periodic VAT Returns using e-invoice 3.0 on the performance of tax revenue at KPP Pratama Manado. The method used in this research is a qualitative research method with a descriptive approach, the data source used is primary data. The results showed that the level of compliance of corporate taxpayers in reporting Periodic VAT returns using e-invoice 3.0 on the performance of tax revenue at KPP Pratama Manado with a percentage of effective and very effective revenue realization because it can be seen from the realization of tax revenue that has increased from period to period and from year to year.